Empowering Cadres in Optimizing Pregnant Women's Nutrition and Monitoring Fetal Well-Being Through Maternal Neonatal Education Model Family Culturally Based - Nur Elly; Rahma Annisa; Dwi Wulandari; Jordan Llego (Asosiasi Profesi Multimedia Indonesia, 2025)
Background: Pregnancy is a significant and eagerly anticipated event within families, closely tied to the cultural values they uphold. As the primary support system for pregnant women, families influence key health behaviors, particularly nutrition and monitoring of fetal well-being. Health workers play a vital role in assisting pregnant women and their families to adapt cultural practices in support of maternal and fetal health.Aims: This study aims to enhance the role of health workers in optimizing maternal nutrition and monitoring fetal well-being through the implementation of a culturally sensitive Family Maternal-Neonatal Education (EMN) model. The specific objective is to empower community health volunteers (cadres) to improve maternal nutrition and monitor fetal well-being effectively.Methods: The implementation adopted a Community Nursing Approach and utilized Community Development (CD) strategies. Cadres participated in persuasive and educational training programs tailored to cultural contexts. These sessions focused on key competencies in maternal nutrition during pregnancy and breastfeeding, as well as techniques for monitoring fetal well-being.Result: Following the training, cadres showed a significant improvement in knowledge related to maternal nutrition and breastfeeding, with an average increase of 10 points in knowledge assessment scores. This improvement supports broader efforts to reduce maternal and infant mortality and prevent stunting in children.Conclusion: Continuous training using a culturally based EMN model is necessary to further strengthen cadre competencies in supporting maternal nutrition and fetal well-being. This approach contributes to sustainable improvements in maternal and neonatal health outcomes within culturally diverse communities.